PISCIS: Platform for Interactive Search and Citizen Science - Daza, I. (2021)
Many topics in modern astronomy are characterised by the identification of features in images. While this is an easy task for a trained eye, it is difficult to obtain the same quality when performed by models or numerical methods. Here we present the experience and development of a citizen science web platform (PÍSCÍS, Platform for Interactive Search and Citizen Science), that aims at generating value-added catalogues from data comprising a set of images. We also show a pilot prroject for the classification of interactions in galaxy pairs using an open web platform.